2020
DOI: 10.1016/j.mehy.2020.109968
|View full text |Cite
|
Sign up to set email alerts
|

The intriguing commonality of NETosis between COVID-19 & Periodontal disease

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 2 publications
0
52
0
6
Order By: Relevance
“…Also, it was suggested that periodontopathic bacteria might enhance SARS‐CoV‐2 virulence by cleaving its S glycoproteins (Madapusi Balaji et al, 2020; Takahashi et al, 2020) and that the oral cavity, and specially periodontal pockets could act as a viral reservoir (Badran et al, 2020; Bao et al, 2020; Botros et al, 2020; Herrera et al, 2020; Kheur et al, 2020). Gupta et al indicated that Neutrophil Extracellular Trap production is involved in the pathogenesis of both diseases (Gupta & Sahni, 2020), and Sahni et al suggested that the strong Th17 response in severe periodontitis could exacerbate the cytokine storm in COVID‐19 (Sahni & Gupta, 2020). All these hypothetical pathways could also foresee an increased incidence of periodontal lesions, especially necrotizing periodontal disease (NPD) during this pandemic (Patel & Woolley, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was suggested that periodontopathic bacteria might enhance SARS‐CoV‐2 virulence by cleaving its S glycoproteins (Madapusi Balaji et al, 2020; Takahashi et al, 2020) and that the oral cavity, and specially periodontal pockets could act as a viral reservoir (Badran et al, 2020; Bao et al, 2020; Botros et al, 2020; Herrera et al, 2020; Kheur et al, 2020). Gupta et al indicated that Neutrophil Extracellular Trap production is involved in the pathogenesis of both diseases (Gupta & Sahni, 2020), and Sahni et al suggested that the strong Th17 response in severe periodontitis could exacerbate the cytokine storm in COVID‐19 (Sahni & Gupta, 2020). All these hypothetical pathways could also foresee an increased incidence of periodontal lesions, especially necrotizing periodontal disease (NPD) during this pandemic (Patel & Woolley, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…По данным ряда авторов, среди пациентов с COVID-19, страдающих ОРДС и нуждающихся в проведении инвазивной ИВЛ, смертность составляет от 24 до 53% [16,20,21]. Тяжесть состояния усугубляется частично из-за дистального слизисто-гнойного секрета, препятствующего свободной вентиляции легких.…”
Section: Discussionunclassified
“…Тяжесть состояния усугубляется частично из-за дистального слизисто-гнойного секрета, препятствующего свободной вентиляции легких. Исследования сыворотки крови и жидкости бронхоальвеолярного лаважа у этих больных выявили высокое содержание НВЛ, которые, в свою очередь, способствуют увеличению вязкости слизисто-гнойной мокроты [16,20,21], что полностью согласуется с полученными нами результатами.…”
Section: Discussionunclassified
“…Cellular release of histones, major mediators of death in sepsis and neutrophil extracellular trap (NET) formation, has been implicated in COVID-19 coagulopathy [8][9][10][11][12]. Histones increase plasma thrombin generation directly through interactions with coagulation proteins [13,14], platelets, neutrophils, and endothelial cells [15,16].…”
Section: Introductionmentioning
confidence: 99%